Framework for Sustainable Management of Shellfish Resources Based on Eco-Biology and Socio-Economic Conditions in Sedati, Sidoarjo, Indonesia - Pursetyo, Kustiawan Tri; Idris, Mohd Hanafi; Zein, Alfian; Masithah, Endang Dewi (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research  Sustainable Management: Developing strategies for the long-term sustainability of shellfish resources in Sedati, Sidoarjo. Eco-Biological Considerations: Emphasizing the role of ecological and biological factors in managing shellfish populations. Socio-Economic Integration: Balancing economic activities and community welfare with the preservation of shellfish resources. Regional Focus: Tailoring management practices specifically to the unique environmental and social conditions of Sedati, Sidoarjo.     Abstract Sedati is one of the subdistricts producing fishery products, namely milkfish, shrimp, and shellfish. Some of the products are further processed generate long-term income. Economic variables profoundly influence shellfish harvesting, as heightened catches immediately enhance fishermen's revenue. Nonetheless, increased income may lead to intensified fishing activities, potentially jeopardizing the viability of shellfish populations if not adequately regulated. This study develop to the framework for sustainable management of shellfish resources based on eco-biology and socio-economic conditions. This research used a survey research method with primary and secondary data. The samples collected from this study were spread across 224 respondents who are fishermen. The hauling process is carried out while catching shellfish 100-150 times. Shellfish fishing activities are carried out 20–26 days a month. This study found that catch factors having no significant effect on sustainable fisheries management, ecological factors and shellfish capture and sustainable fisheries and sustainable fisheries management social factors and the capture of shellfish. Biological factors and shellfish catchment and management economic factors influence the shellfish capture showed significant influence on the fisheries management. The development of this model can serve as a benchmark for shellfish fishing activity in this coastal water. Overfishing or activities in this area can be monitored using this model. The purpose is to control or monitor the stock and the inventory of the shellfish fisheries to preserve them for further use. Economic factors have a significant effect on shellfish caching because the more shellfish caught, the income of shellfish fishermen will directly increase, economic factors also have a significant influence on the sustainable management of shellfish. The greater the income of fishermen, the greater the availability of shellfish stocks will be because the fishing effort carried out by fishermen will be massive. This research in the future can provide information on how to balance ecological, economic, and social factors to ensure the long-term viability of shellfish populations and the ecosystem support.